Fertility Preservation in Endometriosis Patients: Anti-Müllerian Hormone Is a Reliable Marker of the Ovarian Follicle Density - Garavaglia, Elisabetta; Sala, Cinzia; Taccagni, Gianluca; Traglia, Michela; Barbieri, Caterina; Ferrari, Stefano; Candiani, Massimo; Panina-Bordignon, Paola; Toniolo, Daniela (Frontiers in Surgery, 2017)
Objective To analyze the ovarian reserve via measurement of follicular density and anti-Müllerian hormone (AMH) in endometriosis patients participating to a clinical program of cortical ovarian cryopreservation. Design Retrospective analysis of serum AMH levels and prospective investigation of ovarian follicle number. Setting University Hospital. Patient(s) Two hundred and two women with endometriosis and 400 controls. Intervention(s) Blood samples and ovarian biopsies. Main outcome measure(s) Correlation of serum AMH levels and the number of non-growing follicles in the biopsied cortical tissues in endometriosis and control subjects, including age, type of AMH kit, and the laboratory performing the analysis as covariates. Result(s) AMH levels were shown to decrease with age in untreated endometriosis patients (P < 1.0 × 10−5) but they were significantly lower in endometriosis compared to controls only in patients over 36 years old (P = 2.7 × 10−4). The AMH decrease was faster in endometriosis compared to controls (beta = 0.27, P = 4.0 × 10−4). Primordial follicle number decreased with the reduction of AMH levels in both cases and controls (beta = 0.3; P = 0.04). Conclusion AMH is a reliable marker of ovarian reserve in endometriosis patients, and it can predict follicular density in women undergoing ovarian tissue cryopreservation.